SEEKING OF THE RESOURCE-SAVING AND ENVIRONMENT-SPARING TECHNOLOGIES WITHIN RAPE GROWING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In order to obtain high, qualitative and economically profitable rape yield one needs wholesome and integrated manure, with the aim to ensure the plants' needs for nutritive components and to renovate the soil fertility as well. During 2005 - 2007 there was carried research on the increasing rates of potassic mineral fertilizers K0 - K160 against the background of nitrogen fertilizers N80 and N80+40. Using nitrogen fertilizer 80-120 kg ha-1 the obtained yield increase was remarkable indeed: 0.49-1.09 t ha-1. Increased potassium rate K80 - K160 ensured the yield growth up to 0.17–0.42 t ha-1 The highest oil content 48.22-48.89% was ensured by potassium rate K160. Optimal and economically grounded manure rate is N120P60K80 kg ha-1 with the yield level 2.50 t ha-1 and the oil outcome 1086 kg ha-1. In 2007 and 2008 there was carried research on the rates of stick matter AVENTROL (0.7 and 1.0 l ha-1), and its impact on rapeseed yield and quality. In spring rape sowings the yield increase was 0.49-0.78 t ha-1, but in winter rape sowings –0.72-1.03 t ha-1. The seed humidity, at harvest time, was diminished by 2-6 %. The content of oil in seeds increased by 0.52-1.49 %. The use of the preparation AVENTROL ensured the net income: 57,7 - 161,7 EUR ha-1.